THE EFFECTIVENESS OF THE RADEC LEARNING MODEL ASSISTED BY INTERACTIVE GAMES ON MASTERY OF BASIC SCIENCE CONCEPTS IN ELEMENTARY SCHOOLS - Alimuddin, Nurkhaerat; Yeni Suranti, Ni Made; Seprida, Riski (BIOCHEPHY: Journal of Science Education, 2024)
This research aims to measure the effectiveness of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model assisted by interactive games on the mastery of basic science concepts among prospective elementary school teacher students. This research uses quantitative methods with a non-equivalent control group-type experimental design. The research sample was student prospective elementary school teachers at Mataram University who were selected using a purposive sampling technique. Data collection techniques are carried out through objective tests in the form of and post-tests. The research results showed a significant improvement in the experimental group with an average pre-test score of 62.5 increasing to 84.17 in the post-tests. Meanwhile in the control group, the average pre-test score of 63.17 only increased to 68.5. This data proves that the RADEC model assisted by interactive games is more effective in improving mastery of basic science concepts compared to conventional learning methods. The RADEC model has also been proven to increase student engagement, motivation, and critical and creative thinking abilities in line with the demands of 21st-century skills.